Deflections and Strains in Cracked Shafts Due to Rotating Loads: A Numerical and Experimental Analysis - Nicolò Bachschmid; Ezio Tanzi (International Journal of Rotating Machinery)
In this article the deflections of a circular cross-section beam presenting a transverse crack of varying depths caused by various loads (bending, torsion, shear, and axial loads) are analyzed with the aid of a rather refined three-dimensional model that takes into account the nonlinear contact forces in the cracked area. The bending and shear loads are applied in several different angular positions in order to simulate a rotating load on a fixed beam or, by changing the reference system, a fixed load on a rotating beam. Torsion and axial loads are fixed with respect to the beam.